More counselling for end-of-life decisions by GPs with own advance directives: A postal survey among German general practitioners. (1st January 2018) - Schnakenberg, Rieke; Radbruch, Lukas; Kersting, Christine; Frank, Friederike; Wilm, Stefan; Becka, Denise; Weckbecker, Klaus; Bleckwenn, Markus; Just, Johannes M.; Pentzek, Michael; Weltermann, Birgitta
Abstract: Background: Although general practitioners (GPs) are among the preferred contact persons for discussing end-of-life issues including advance directives (ADs), there is little data on how GPs manage such consultations. Objectives: This postal survey asked German GPs about their counselling for end-of-life decisions. Methods: In 2015, a two-sided questionnaire was mailed to 959 GPs. GPs were asked for details of their consultations on ADs: frequency, duration, template use, and whether they have own ADs. Statistical analysis evaluated physician characteristics associated with an above-average number of consultations on AD. Results: The participation rate was 50.3% ( n  = 482), 70.5% of the GPs were male; the average age was 54 years. GPs had an average of 18 years of professional experience, and 61.4% serve more than 900 patients per three months. Most (96.9%) GPs perform consultations on living wills (LW) and/or powers of attorney (PA), mainly in selected patients (72.3%). More than 20 consultations each on LWs and PAs are performed by 60% and 50% of GPs, respectively. The estimated mean duration of consultations was 21 min for LWs and 16 min for PAs. Predefined templates were used in 72% of the GPs, 50% of GPs had their ADs. A statistical model showed that GPs with ADs and/or a qualification in palliative medicine were more likely to counsel ≥20 patients per year for each document. Conclusion: The study confirmed that nearly all German GPs surveyed provide counselling on ADs. Physicians with ADs counsel more frequently than those without such documents.